The impact of adoption of the XBRL on the development of stock markets / Wafa Sassi, Hakim Ben Othman and Khaled Hussainey - Sassi, Wafa; Ben Othman, Hakim; Hussainey, Khaled (Universiti Teknologi MARA, 2021)
The paper examines the impact of adoption of the eXtensible Business Reporting Language (XBRL) on the development of stock markets using a large international sample. Our analysis was based on panel estimation techniques for 18 countries for a period of 20 years from 2000 to 2019. Our analysis provided empirical evidence that the adoption of the XBRL has a negative impact on the development of stock markets. This implies that strict policies are needed for the successful adoption of the XBRL and also a mechanism is needed to ensure that stakeholders understand the value of the information provided by the XBRL formatted financial reports.